不同矿石对反渗透淡化水的调质效果研究(Effect of different ores on water quality adjustment of seawater desalinated by reverse osmosis) - CHENHong(陈红); YANGXu(阳旭); ZHAOLiqin(赵丽芹); XUBailong(徐百龙); GANShu(甘树); YANGYueping(杨岳平) (Zhejiang Daxue xuebao. Lixue ban, 2016)
In many places, reverse osmosis seawater desalination plays an important role in solving freshwater crisis. In spite of its superior quality, instability of desalinated water may be corrosive to water distribution systems, thus may pose a threat on human health. To solve this problem, four ores were used to adjust the quality of the desalinated water. The physical and chemical properties of maifanshi, dolomite, limestone and an imported ore, including composition, XRD (X-ray Diffraction), porosity and pore size distribution, surface morphology were analyzed. Based on these properties, the effects of the four ores on water quality adjustment of the desalinated water by reverse osmosis were studied. The results indicate that the porosity and dissolution of the imported ore are improved obviously after the artificial process. The hardness, alkalinity, Mg2+ contents of the import ore are 50% higher than any other ores, while the pH value of the effluent is too high, the Ca2+ content in the effluent is lower than that of limestone. Still, there is a certain gap compared with the tap water. In the future, research should focus on the development of modifying agents with large surface areas and faster dissolution rate, which can adjust the desalinated water without acidifying the influent.